Association between cervical spine clinical active range of motion and pain or disability in people with neuromusculoskeletal neck pain: A systematic review and meta-analysis - Saghar Soltanabadi; Sima Vatandoost; Mohammad Bayattork; Michael J. Lukacs; Alison Rushton; David M. Walton (PLoS ONE, 2026)
Objectives To quantify the association between clinical cervical active range of motion and patient-reported outcomes of pain and disability in people with neuromusculoskeletal neck pain. Design Systematic review and meta-analysis following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, registered with PROSPERO (CRD42023417317). Methods A comprehensive search of six databases and grey literature up to December 2024 identified observational studies reporting cross-sectional correlations between active range of motion and patient-reported outcomes in adults with neck pain. Risk of bias was assessed using an adapted National Institutes of Health quality assessment tool. Eight meta-analyses were conducted using random-effects models. Heterogeneity, subgroup analyses (acute versus chronic neck pain, whiplash-related versus non-traumatic), and meta-regressions (age, sex, publication year, risk of bias) were performed. Certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation approach. Results 45 studies (total N = 3,494) were included. Meta-analyses showed statistically significant small to moderate negative correlations (r = −0.21 to −0.34) between active range of motion and patient-reported outcomes in all planes of motion, with stronger associations in acute and whiplash-related neck pain. Substantial heterogeneity (I 2 = 67–91%) was partly explained by symptom duration and mechanism of onset. Certainty of evidence was very low due to risk of bias, inconsistency, and imprecision. Conclusions Cervical active range of motion is modestly associated with pain and disability, especially in acute and traumatic neck pain. Findings should be interpreted with caution. Standardized measurement protocols and higher-quality studies are needed to inform practice.